Improving Learning Outcomes Through Problem Based Learning Model Assisted by Wordwall Media in Pancasila Education in Third Grade Students of Elementary School - Prandini Dianita Riski; Ria Apriani; Denny Hotnida Tampubolon (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
This research aims to improve learning outcomes through the Problem-Based Learning Model assisted by Wordwall Media in Class III Pancasila Education Lessons at SD Negeri 37 Bengkulu City. The research subjects were the teachers and students of Grade III at SD Negeri 37 Bengkulu City, with 30 students. Data collection techniques involved observation and tests. This classroom action research was conducted in two cycles. The research results show an improvement in the learning process and enhancement in each cycle. Only 13 out of 30 students achieved mastery in the pre-cycle phase, representing 43.33%. In Cycle I, 21 out of 30 students reached mastery, with a percentage of 70%. This increased in Cycle II to 27 out of 30 students, with a rate of 90%. Therefore, the research process, using the Problem-Based Learning model assisted by Wordwall media, was deemed successful and well-executed according to the plan, thus concluding the research without needing further cycles, as the success indicator had already been met.